Rational Choice, Agency and Thoughtfully Reflective Decision Making: The Short and Long-Term Consequences of Making Good Choices - Paternoster, Raymond (Journal of quantitative criminology, 2009)
Notions of human agency are a prominent part of some but not all criminological theories. For example, McCarthy (Annu Rev Sociol 28:417–442, 2002) argues that rational choice theory, which allows persons great involvement in decision making, is more congenial with notions of human agency than others. It would appear from his argument that rational choice theory offers fertile ground to develop a clearly defined role for human agency in criminal behavior. In this paper we have taken up McCarthy’s view and argue that an important part of what is human agency consists of thoughtfully reflective decision making. We outline four elements of thoughtfully reflective decision making, and claim that it is a characteristic that varies both across persons and within persons over time. It is in short the process by which good decisions are made because by using this process one increases the likelihood that choices made will be consistent with preferences. We develop a clear operational definition of thoughtfully reflective decision making and link it to the concept of human agency. We also articulate testable hypotheses about the short-term and longer-term implications of thoughtfully reflective decision making. We conclude with a discussion of what we think lies ahead for future conceptual and empirical work.